DESTINATION IMAGE AND INTENTION TO RECOMMEND: THE MEDIATING ROLE OF INTENTION TO REVISIT - Burhanudin, Burhanudin; Ariani, Shabrina (Universitas Pakuan, 2023)
ABSTRACTThis study empirically examines the influence of destination image and intention to revisit on intention to recommend and the mediating role of intention to revisit in the relationship between destination image and intention to recommend. The research focuses on Sunan Ampel religious tourism site visitors in Surabaya, utilizing non-probability sampling with the purposive sampling method. The sample consists of individuals who have previously visited a religious site in Surabaya, Indonesia. There were 267 respondents participated in this study. This study found destination image has a significant influence on the intention to revisit and the intention to recommend. Furthermore, the intention to revisit significantly affects the intention to recommend. Finally, destination image significantly influences the intention to recommend through the mediating role of intention to revisit. Suggestions for religious tourism managers include stimulating tourists to have a high intention to recommend by providing easy access and comprehensive information. Improvements in facilities should be made to ensure that tourists can comfortably utilize them.ABSTRAKPenelitian ini bertujuan untuk menguji secara empiris pengaruh destination image, intention to revisit terhadap intention to recommend serta peran intention to revisit sebagai mediator antara destination image dan intention to recommend. Responden penelitian adalah pengunjung wisata religi Sunan Ampel Surabaya, menggunakan metode non-probability sampling dengan purposive sampling. Sampel dalam penelitian ini adalah wisatawan yang pernah berkunjung ke sebuah wisata religi di Surabaya, Indonesia. Terdapat 267 responden pada penelitian ini. Penelitian ini menemukan destination image berpengaruh signifikan terhadap intention to revisit dan intention to recommend. Temuan lain adalah Intention to revisit berpengaruh signifikan terhadap intention to recommend. Temuan selanjutnya destination image berpengaruh signifikan terhadap intention to recommend melalui intention to revisit. Bagi pengelola wisata religi dapat memicu wisatawan untuk timbul intention to recommend yang tinggi dengan memberikan kemudahan akses dan informasi. Perbaikan terhadap fasilitas juga perlu dilakukan agar wisatawan merasa lebih nyaman saat berkunjung.